SGP-C: A Broad Host Range Temperate Bacteriophage; Against Salmonella gallinarum - Ilyas, Syeda Zainab; Tariq, Hafsa; Basit, Abdul; Tahir, Hamza; Haider, Zulquernain; Rehman, Shafiq ur (Frontiers in Microbiology, 2022)
Salmonella Gallinarum is a poultry restricted-pathogen causing fowl-typhoid disease in adult birds with mortality rates up-to 80% and exhibit resistance against commonly used antibiotics. In current study, a temperate broad host range bacteriophage SGP-C was isolated against S. Gallinarum from poultry digesta. It showed infection ability in all the 15 tested field strains of S. Gallinarum. The SGP-C phage produced circular, turbid plaques with alternate rings. Its optimum activity was observed at pH 7.0 and 37-42℃, with a latent period of 45 minutes and burst size of 187virions/bacterial cell. The SGP-C lysogens, SGPC-L5 and SGPC-L6 exhibited super-infection immunity against the same phage, an already reported feature of lysogens. A virulence index of 0.5 and 0.001 as MV50 of SGP-C suggests its moderate virulence. The genome of SGP-C was found circular double stranded DNA of 42Kbp with 50.04% GC content, which encodes 63 ORFs. The presence of repressor gene at ORF49, and absence of tRNA sequence in SGP-C genome indicates its lysogenic nature. Furthermore, from NGS analysis of lysogens we propose that SGP-C genome might exist either as an episome, or both as integrated and temporary episome in the host cell and warrants further studies. Phylogenetic analysis revealed its similarity with Salmonella temperate phages belonging to family Siphoviridae. The encoded proteins by SGP-C genome have not showed homology with any known toxin and virulence factor. Although plenty of lytic bacteriophages against this pathogen are already reported, to our knowledge SGP-C is the first lysogenic phage against S. Gallinarum reported so far.